2021
DOI: 10.1097/mlr.0000000000001523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Affordable Care Act Medicaid Expansion on the Distribution of New General Internists Across States

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…This, in turn, can reduce the supply of new PCPs in nonexpansion states as noted by prior research. 7 Indeed, a recent study published in Medical Care found that the Medicaid expansion was associated with more new general internists choosing to practice in expansion states instead of nonexpansion states. 7 It will be interesting for future studies to examine whether the increased starting pay together with other ACA provisions directly targeting primary care (such as investment in continued development of primary care workforce) 30 enhanced the job satisfaction of PCPs in expansion states, and whether the change in new PCPs' distribution, especially new general internists, ultimately leads to better access to primary care and better health outcomes for people in expansion states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, can reduce the supply of new PCPs in nonexpansion states as noted by prior research. 7 Indeed, a recent study published in Medical Care found that the Medicaid expansion was associated with more new general internists choosing to practice in expansion states instead of nonexpansion states. 7 It will be interesting for future studies to examine whether the increased starting pay together with other ACA provisions directly targeting primary care (such as investment in continued development of primary care workforce) 30 enhanced the job satisfaction of PCPs in expansion states, and whether the change in new PCPs' distribution, especially new general internists, ultimately leads to better access to primary care and better health outcomes for people in expansion states.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Studies of the effect of the Medicaid expansion on primary care and behavioral health workforce have also emerged in recent years. [5][6][7] In terms of primary care workforce, a recent study showed that new general internists increasingly chose to practice in expansion states after the expansion was implemented. 7 A qualitative study found that health care organizations in expansion states tried to recruit more primary care providers to meet the higher demand for health care.…”
mentioning
confidence: 99%
“…Previously, smart communities have been studied primarily from the aspects of advanced computer technologies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], design of operating modes [ 16 , 17 , 18 , 19 ], and governance in the implementation of the smart community [ 4 , 5 , 20 , 21 , 22 , 23 ]. Moreover, there are many kinds of studies on residents’ demands, most of which concentrate on a specific aspect, such as energy demand [ 24 , 25 ], elderly care services [ 26 , 27 ], medical care services [ 28 , 29 ], urban green space [ 30 , 31 ], public sports services [ 32 ], and housing demand [ 30 , 33 ]. However, relevant studies still suffer some limitations, which are embodied in the following three aspects.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Medical Care 8 assessed whether the fact that some states expanded Medicaid while other did not influenced the choice of states where new physicians, defined as those just completing graduate medical education (GME), in 8 specialty groups established their first practices. The study found that higher numbers of new general internists established their first practices in expansion states than would have if every state had expanded, meaning that expansion states gained new general internists, while nonexpansion states lost them.…”
mentioning
confidence: 99%